A method for treating a wear-resistant motor housing
By using cerium-doped electrolyte doped particles and modification treatment technology on the aluminum alloy motor shell, a high hardness and wear resistance coating is formed, which solves the problem of low surface hardness of the aluminum alloy motor shell and improves the heat dissipation of the motor and work efficiency.
Patent Information
- Application Number
- CN202411572128.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The surface hardness of the aluminum alloy motor housing is low, which leads to impervious wear resistance and affects the motor's heat dissipation and working efficiency.
By doping cerium into the zirconium oxide, electroless doped particles with high specific surface area are obtained, and these particles are added during the plating process, combining the modification of 3-(trihydroxysilyl)-1-propanesulfonic acid Treatment and pretreatment of glycine, O-methylisourea sulfate to form a stable and dense doped particles-containing tin plating layer.
It significantly improves the hardness and wear resistance of the motor housing surface, and enhances the motor's heat dissipation ability and working efficiency.
Smart Images

Figure WKZ3UOGMLL8RB0DTX8T92OR2AXZOMYAW0WVP4PBK
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material plating, and in particular to a method for processing a wear-resistant motor housing. Background Art
[0002] When the motor is running, if the heat dissipation is not good, the internal temperature of the motor will continue to rise and may exceed the designed operating temperature, resulting in damage to the insulation material, causing the multi-pole copper wire to short-circuit and burn the motor. In addition, high temperature will increase the resistance of the motor, resulting in increased power loss and reduced efficiency. Therefore, magnesium alloy or aluminum alloy with good thermal conductivity is usually used as the motor shell, which improves the heat dissipation capacity of the motor and effectively avoids the heat accumulation of the motor, thereby ensuring the working efficiency and stable performance of the motor under working conditions. However, aluminum alloy or magnesium alloy generally has low hardness and is prone to wear during processing, assembly or use. Summary of the invention
[0003] To this end, the present invention provides a method for treating a wear-resistant motor housing, the steps comprising:
[0004] (1) preparing an aqueous solution of cerium nitrate; adding ammonium carbonate to ammonia water to prepare a precipitant; stirring the aqueous solution of cerium nitrate, adding hydrogen peroxide to the solution under stirring, continuing to stir the solution to mix evenly after adding, then adding zirconium oxynitrate to the solution under stirring, stirring and mixing evenly after adding, then adding the precipitant to the solution under stirring, heating to 60-90° C. in a water bath after adding, stirring and precipitating, separating the solid from the liquid, washing the solid phase with deionized water, and then calcining at 560-600° C. for 1-2 hours to obtain a composite oxide powder;
[0005] (2) preparing an ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid; immersing the composite oxide powder in ethanol, dispersing it by ultrasonic stirring to obtain a suspension, then heating the suspension in a water bath to 40±5° C. and keeping it warm, condensing and refluxing during the insulation process; then adding the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid to the suspension under stirring, and continuing to stir at a constant temperature of 40±5° C. for more than 18 hours after the addition is completed, then separating the solid from the liquid, washing the solid phase with deionized water, and drying to obtain chemically plated doped particles;
[0006] (3) preparing an aqueous solution of glycine and an aqueous solution of O-methylisourea sulfate; stirring the aqueous solution of glycine, adding the aqueous solution of O-methylisourea sulfate and the aqueous solution of lithium hydroxide to the solution under stirring, and after the addition is completed, ice-bathing to 0-5° C. and maintaining the temperature, stirring at the constant temperature for more than 20 hours; then adding sodium nitrate and sodium nitrite, stirring for more than 30 minutes to obtain a treated solution;
[0007] (4) The aluminum alloy motor housing is polished with sandpaper to remove the oxide scale, and then degreased with a degreasing agent. After taking it out, the residual degreasing agent is blown away with an air gun, and then immersed in a dilute nitric acid solution for pickling activation. After activation, the clean acid solution is taken out, and the residual solution is blown away, and then immersed in the treatment solution at a constant temperature of 50 to 70° C. for 4 to 5 minutes to obtain a pre-treated housing;
[0008] (5) preparing a chemical plating solution, wherein the components of the chemical plating solution are nickel sulfate, sodium hypophosphite, the chemical plating doping particles, potassium iodide, trisodium citrate, thiourea and ammonium acetate, and the solvent is water; adjusting the pH of the chemical plating solution to 3.5-4.5 with hydrochloric acid or sodium hydroxide solution, and maintaining the temperature at 85±5°C in a water bath; then immersing the pretreated housing in the chemical plating solution, plating at a constant temperature of 85±5°C for 1-2 hours, testing the pH of the plating solution every 5-15 minutes, and adjusting the pH of the plating solution to 3.5-4.5 with hydrochloric acid or sodium hydroxide solution; taking out the housing after the chemical plating is completed, rinsing with clean water to remove the residual liquid on the surface of the housing, and drying the housing to obtain the wear-resistant motor housing.
[0009] Furthermore, in the step (1), the concentration of cerium nitrate in the aqueous solution of cerium nitrate is 20-25 g / L, and the solvent is water; the amount ratio of ammonium carbonate added to ammonia water to prepare a precipitant is ammonium carbonate: ammonia water = 2-3 g: 100 mL, and the mass percentage of solute in the ammonia water is 25%; the amount ratio of the aqueous solution of cerium nitrate, hydrogen peroxide, zirconium oxynitrate, and precipitant is cerium nitrate aqueous solution: hydrogen peroxide: zirconium oxynitrate: precipitant = 100 mL: 6-8 mL: 7-8 g: 10-15 mL; wherein the mass percentage of solute in the hydrogen peroxide is 5%.
[0010] Furthermore, in the step (2), in the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid, the concentration of 3-(trihydroxysilyl)-1-propanesulfonic acid is 2 to 3 g / 100 mL, and the solvent is ethanol; the amount ratio of the composite oxide powder immersed in ethanol is composite oxide powder: ethanol = 1 to 2 g: 50 mL; the volume ratio of adding the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid to the suspension is suspension: ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid = 1:1.
[0011] Furthermore, in the step (3), in the aqueous solution of glycine, the concentration of glycine is 16-18 g / 100 mL, and the solvent is water; in the aqueous solution of O-methylisourea sulfate, the concentration of O-methylisourea sulfate is 20-23 g / 100 mL, and the solvent is water; in the aqueous solution of lithium hydroxide, the concentration of lithium hydroxide is 5-6 g / 100 mL, and the solvent is water; the amount ratio of the aqueous solution of glycine, the aqueous solution of O-methylisourea sulfate, the aqueous solution of lithium hydroxide, sodium nitrate and sodium nitrite is glycine aqueous solution: O-methylisourea sulfate aqueous solution: lithium hydroxide aqueous solution: sodium nitrate: sodium nitrite = 100 mL: 100 mL: 40-50 mL: 8-10 g: 3-5 g.
[0012] Furthermore, in step (4), the concentration of the solute in the dilute nitric acid solution is 1%.
[0013] Furthermore, in step (5), the concentration of each component in the chemical plating solution is: nickel sulfate 24-26 g / L, sodium hypophosphite 28-30 g / L, chemical plating doping particles 1-2 g / L, potassium iodide 3-5 mg / L, trisodium citrate 15-20 g / L, thiourea 0.5 mg / L, ammonium acetate 18-20 g / L; the mass percentage of hydrochloric acid solute used to adjust the pH of the plating solution is 30%, the mass percentage of sodium hydroxide solution solute is 30%, and the solvent is water.
[0014] The beneficial effect of the present invention is that after the high thermal conductivity aluminum alloy motor housing is treated by the method of the present invention, the problem of low surface hardness and poor wear resistance of the aluminum alloy is solved, and the surface hardness is significantly improved. By comparing Example 3 of the present invention and the comparative examples, it can be seen that by adding chemical plating doping particles during the plating process, or pre-treating the surface of the aluminum alloy substrate before plating, the surface hardness of the coating can be significantly improved. This is mainly because: the present invention first obtains chemical plating doping particles with a high specific surface area by doping cerium in zirconium oxide, so that the bonding surface between the doped particles and the coating in the subsequent coating is larger and the bonding is more firm, and the doping of cerium is conducive to optimizing the surface state of the particles, providing conditions for the subsequent modification process of the particles. The particles are then modified by 3-(trihydroxysilyl)-1-propanesulfonic acid to form sulfonic acid functional groups on the particle surface, which is beneficial to the binding and deposition of the particles on the surface of the motor housing during subsequent plating. In addition, the motor housing is pretreated by glycine, O-methylisourea sulfate, etc. to form an amino-containing pretreatment layer on the housing surface, which is more conducive to the formation of the coating and the adsorption of chemically plated doped particles during the plating process, forming a stable and dense tin-plated coating containing doped particles, thereby improving the wear resistance of the housing surface. DETAILED DESCRIPTION
[0015] The present invention will be further described below in conjunction with the embodiments.
[0016] Example 1
[0017] A method for treating a wear-resistant motor housing, comprising the steps of:
[0018] (1) preparing an aqueous solution of cerium nitrate; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 20 g / L, and the solvent is water; adding ammonium carbonate to ammonia water to prepare a precipitant; the amount ratio of ammonium carbonate to ammonia water to prepare a precipitant is ammonium carbonate: ammonia water = 2 g: 100 mL, and the mass percentage of solute in the ammonia water is 25%; stirring the aqueous solution of cerium nitrate, adding hydrogen peroxide to the solution under stirring, continuing to stir the solution for 10 minutes after adding, and then adding zirconium oxynitrate to the solution under stirring, and stirring for another 10 minutes after adding. n, then add the precipitant to the solution under stirring, wherein the amount ratio of the aqueous solution of cerium nitrate, hydrogen peroxide, zirconium oxynitrate and precipitant is the aqueous solution of cerium nitrate: hydrogen peroxide: zirconium oxynitrate: precipitant = 100mL: 6mL: 7g: 10mL; wherein the mass percentage of the solute in the hydrogen peroxide is 5%; after adding the materials, heat in a water bath to 85°C, keep warm and stir for 3h, condense and reflux during the heat preservation process; precipitate, separate the solid and liquid, wash the solid phase with deionized water 3 times, and then calcine at 560°C for 1h to obtain a composite oxide powder;
[0019] (2) preparing an ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid; in the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid, the concentration of 3-(trihydroxysilyl)-1-propanesulfonic acid is 2 g / 100 mL, and the solvent is ethanol; soaking the composite oxide powder in ethanol, and the ratio of the composite oxide powder to ethanol is 1 g: 50 mL; stirring and dispersing with ultrasonic wave for 20 minutes to obtain a suspension, and then The suspension is heated to 40° C. in a water bath and condensed and refluxed during the insulation process; the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid is added to the suspension under stirring, and the volume ratio of the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid to the suspension is 1:1; after the addition is completed, the stirring is continued at a constant temperature of 40° C. for 18 hours, and then the solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and dried at 80° C. for 10 hours to obtain chemically plated doped particles;
[0020] (3) Prepare an aqueous solution of glycine, wherein the concentration of glycine in the aqueous solution of glycine is 16 g / 100 mL, and the solvent is water; prepare an aqueous solution of O-methylisourea sulfate; wherein the concentration of O-methylisourea sulfate in the aqueous solution of O-methylisourea sulfate is 20 g / 100 mL, and the solvent is water; stir the aqueous solution of glycine, add the aqueous solution of O-methylisourea sulfate and the aqueous solution of lithium hydroxide to the solution under stirring, and after the addition is completed, ice bath to 3° C. for insulation, and stir at a constant temperature for 20 hours; add sodium nitrate and sodium nitrite, wherein the concentration of lithium hydroxide in the aqueous solution of lithium hydroxide is 5 g / 100 mL, and the solvent is water; the amount ratio of the aqueous solution of glycine, the aqueous solution of O-methylisourea sulfate, the aqueous solution of lithium hydroxide, sodium nitrate and sodium nitrite is the aqueous solution of glycine: the aqueous solution of O-methylisourea sulfate: the aqueous solution of lithium hydroxide: sodium nitrate: sodium nitrite = 100 mL: 100 mL: 40 mL: 8 g: 3 g; stir for 30 minutes to obtain a treated solution;
[0021] (4) The aluminum alloy (2A12 aluminum alloy) motor housing is sanded to remove the oxide scale, then immersed in acetone for 10 minutes for degreasing treatment, and after being taken out, the residual acetone is blown dry with an air gun, and immersed in a dilute nitric acid solution for 20 seconds for pickling activation, wherein the concentration of the solute in the dilute nitric acid solution is 1%; after activation, it is taken out and immersed in deionized water for ultrasonic immersion for 5 minutes, and then the residual liquid is taken out and blown dry, and immersed in the treatment solution at a constant temperature of 60° C. for 5 minutes to obtain a pre-treated housing;
[0022] (5) preparing a chemical plating solution, wherein the components of the chemical plating solution are nickel sulfate, sodium hypophosphite, the chemical plating doping particles, potassium iodide, trisodium citrate, thiourea and ammonium acetate, and the solvent is water; the concentrations of the components are: nickel sulfate 24 g / L, sodium hypophosphite 28 g / L, chemical plating doping particles 1 g / L, potassium iodide 3 mg / L, trisodium citrate 15 g / L, thiourea 0.5 mg / L, ammonium acetate 18 g / L; adjusting the pH of the plating solution to 4 with hydrochloric acid or sodium hydroxide solution, and using The mass percentage of hydrochloric acid solute for adjusting the pH of the plating solution is 30%, the mass percentage of sodium hydroxide solution solute is 30%, and the solvent is water; the water bath is kept at a constant temperature of 85° C.; the pretreated shell is then immersed in the chemical plating solution, and the plating is carried out at a constant temperature of 85° C. for 1 hour, the pH of the plating solution is tested every 10 minutes, and the pH of the plating solution is adjusted to 4 with hydrochloric acid or sodium hydroxide solution; after the chemical plating is completed, it is taken out, rinsed with clean water to remove the residual liquid on the surface of the shell, and blown dry to obtain the wear-resistant motor shell.
[0023] Example 2
[0024] A method for treating a wear-resistant motor housing, comprising the steps of:
[0025] (1) preparing an aqueous solution of cerium nitrate; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 22 g / L, and the solvent is water; adding ammonium carbonate to ammonia water to prepare a precipitant; the amount ratio of ammonium carbonate to ammonia water to prepare a precipitant is ammonium carbonate: ammonia water = 2 g: 100 mL, and the mass percentage of solute in the ammonia water is 25%; stirring the aqueous solution of cerium nitrate, adding hydrogen peroxide to the solution under stirring, continuing to stir the solution for 10 minutes after adding, and then adding zirconium oxynitrate to the solution under stirring, and stirring for another 10 minutes after adding. n, then add the precipitant to the solution under stirring, wherein the amount ratio of the aqueous solution of cerium nitrate, hydrogen peroxide, zirconium oxynitrate and precipitant is the aqueous solution of cerium nitrate: hydrogen peroxide: zirconium oxynitrate: precipitant = 100mL: 7mL: 7g: 12mL; wherein the mass percentage of the solute in the hydrogen peroxide is 5%; after adding the materials, heat in a water bath to 85°C, keep warm and stir for 3h, condense and reflux during the heat preservation process; precipitate, separate the solid and liquid, wash the solid phase with deionized water 3 times, and then calcine at 560°C for 1h to obtain a composite oxide powder;
[0026] (2) preparing an ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid; in the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid, the concentration of 3-(trihydroxysilyl)-1-propanesulfonic acid is 2 g / 100 mL, and the solvent is ethanol; soaking the composite oxide powder in ethanol, and the ratio of the composite oxide powder to ethanol is 1 g: 50 mL; stirring and dispersing with ultrasonic wave for 20 minutes to obtain a suspension, and then The suspension is heated to 40° C. in a water bath and condensed and refluxed during the insulation process; the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid is added to the suspension under stirring, and the volume ratio of the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid to the suspension is 1:1; after the addition is completed, the stirring is continued at a constant temperature of 40° C. for 18 hours, and then the solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and dried at 80° C. for 10 hours to obtain chemically plated doped particles;
[0027] (3) Prepare an aqueous solution of glycine, wherein the concentration of glycine in the aqueous solution of glycine is 17 g / 100 mL, and the solvent is water; prepare an aqueous solution of O-methylisourea sulfate; wherein the concentration of O-methylisourea sulfate in the aqueous solution of O-methylisourea sulfate is 21 g / 100 mL, and the solvent is water; stir the aqueous solution of glycine, add the aqueous solution of O-methylisourea sulfate and the aqueous solution of lithium hydroxide to the solution under stirring, and after the addition is completed, ice bath to 3° C. for insulation, and stir at a constant temperature for 20 hours; add sodium nitrate and sodium nitrite, wherein the concentration of lithium hydroxide in the aqueous solution of lithium hydroxide is 5 g / 100 mL, and the solvent is water; the amount ratio of the aqueous solution of glycine, the aqueous solution of O-methylisourea sulfate, the aqueous solution of lithium hydroxide, sodium nitrate and sodium nitrite is the aqueous solution of glycine: the aqueous solution of O-methylisourea sulfate: the aqueous solution of lithium hydroxide: sodium nitrate: sodium nitrite = 100 mL: 100 mL: 40 mL: 9 g: 4 g; stir for 30 minutes to obtain a treated solution;
[0028] (4) The aluminum alloy (2A12 aluminum alloy) motor housing is sanded to remove the oxide scale, then immersed in acetone for 10 minutes for degreasing treatment, and after being taken out, the residual acetone is blown dry with an air gun, and immersed in a dilute nitric acid solution for 20 seconds for pickling activation, wherein the concentration of the solute in the dilute nitric acid solution is 1%; after activation, it is taken out and immersed in deionized water for ultrasonic immersion for 5 minutes, and then the residual liquid is taken out and blown dry, and immersed in the treatment solution at a constant temperature of 60° C. for 5 minutes to obtain a pre-treated housing;
[0029] (5) preparing a chemical plating solution, wherein the components of the chemical plating solution are nickel sulfate, sodium hypophosphite, the chemical plating doping particles, potassium iodide, trisodium citrate, thiourea and ammonium acetate, and the solvent is water; the concentrations of the components are: nickel sulfate 25 g / L, sodium hypophosphite 29 g / L, chemical plating doping particles 1 g / L, potassium iodide 4 mg / L, trisodium citrate 17 g / L, thiourea 0.5 mg / L, ammonium acetate 19 g / L; adjusting the pH of the plating solution to 4 with hydrochloric acid or sodium hydroxide solution, and using The mass percentage of hydrochloric acid solute for adjusting the pH of the plating solution is 30%, the mass percentage of sodium hydroxide solution solute is 30%, and the solvent is water; the water bath is kept at a constant temperature of 85° C.; the pretreated shell is then immersed in the chemical plating solution, and the plating is carried out at a constant temperature of 85° C. for 1 hour, the pH of the plating solution is tested every 10 minutes, and the pH of the plating solution is adjusted to 4 with hydrochloric acid or sodium hydroxide solution; after the chemical plating is completed, it is taken out, rinsed with clean water to remove the residual liquid on the surface of the shell, and blown dry to obtain the wear-resistant motor shell.
[0030] Example 3
[0031] A method for treating a wear-resistant motor housing, comprising the steps of:
[0032] (1) preparing an aqueous solution of cerium nitrate; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 24 g / L, and the solvent is water; adding ammonium carbonate to ammonia water to prepare a precipitant; the amount ratio of ammonium carbonate to ammonia water to prepare a precipitant is ammonium carbonate: ammonia water = 3 g: 100 mL, and the mass percentage of solute in the ammonia water is 25%; stirring the aqueous solution of cerium nitrate, adding hydrogen peroxide to the solution under stirring, continuing to stir the solution for 10 minutes after adding, and then adding zirconium oxynitrate to the solution under stirring, and stirring for another 10 minutes after adding. n, then add the precipitant to the solution under stirring, wherein the amount ratio of the aqueous solution of cerium nitrate, hydrogen peroxide, zirconium oxynitrate and precipitant is the aqueous solution of cerium nitrate: hydrogen peroxide: zirconium oxynitrate: precipitant = 100mL: 7mL: 8g: 14mL; wherein the mass percentage of the solute in the hydrogen peroxide is 5%; after adding the materials, heat to 85°C in a water bath, keep warm and stir for 3h, condense and reflux during the heat preservation process; precipitate, separate the solid and liquid, wash the solid phase with deionized water 3 times, and then calcine at 560°C for 1h to obtain a composite oxide powder;
[0033] (2) preparing an ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid; in the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid, the concentration of 3-(trihydroxysilyl)-1-propanesulfonic acid is 3 g / 100 mL, and the solvent is ethanol; soaking the composite oxide powder in ethanol, and the amount ratio of the composite oxide powder to ethanol is composite oxide powder: ethanol = 1 g: 50 mL; stirring and dispersing with ultrasonic wave for 20 minutes to obtain a suspension, and then The suspension is heated to 40° C. in a water bath and condensed and refluxed during the insulation process; the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid is added to the suspension under stirring, and the volume ratio of the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid to the suspension is 1:1; after the addition is completed, the stirring is continued at a constant temperature of 40° C. for 18 hours, and then the solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and dried at 80° C. for 10 hours to obtain chemically plated doped particles;
[0034] (3) Prepare an aqueous solution of glycine, wherein the concentration of glycine in the aqueous solution of glycine is 17 g / 100 mL, and the solvent is water; prepare an aqueous solution of O-methylisourea sulfate; wherein the concentration of O-methylisourea sulfate in the aqueous solution of O-methylisourea sulfate is 22 g / 100 mL, and the solvent is water; stir the aqueous solution of glycine, add the aqueous solution of O-methylisourea sulfate and the aqueous solution of lithium hydroxide to the solution under stirring, and after the addition is completed, ice bath to 3° C. for insulation, and stir at a constant temperature for 20 hours; add sodium nitrate and sodium nitrite, wherein the concentration of lithium hydroxide in the aqueous solution of lithium hydroxide is 6 g / 100 mL, and the solvent is water; the amount ratio of the aqueous solution of glycine, the aqueous solution of O-methylisourea sulfate, the aqueous solution of lithium hydroxide, sodium nitrate and sodium nitrite is the aqueous solution of glycine: the aqueous solution of O-methylisourea sulfate: the aqueous solution of lithium hydroxide: sodium nitrate: sodium nitrite = 100 mL: 100 mL: 50 mL: 9 g: 4 g; stir for 30 minutes to obtain a treated solution;
[0035] (4) The aluminum alloy (2A12 aluminum alloy) motor housing is sanded to remove the oxide scale, then immersed in acetone for 10 minutes for degreasing treatment, and after being taken out, the residual acetone is blown dry with an air gun, and immersed in a dilute nitric acid solution for 20 seconds for pickling activation, wherein the concentration of the solute in the dilute nitric acid solution is 1%; after activation, it is taken out and immersed in deionized water for ultrasonic immersion for 5 minutes, and then the residual liquid is taken out and blown dry, and immersed in the treatment solution at a constant temperature of 60° C. for 5 minutes to obtain a pre-treated housing;
[0036] (5) preparing a chemical plating solution, wherein the components of the chemical plating solution are nickel sulfate, sodium hypophosphite, the chemical plating doping particles, potassium iodide, trisodium citrate, thiourea and ammonium acetate, and the solvent is water; the concentrations of the components are: nickel sulfate 25 g / L, sodium hypophosphite 29 g / L, chemical plating doping particles 2 g / L, potassium iodide 4 mg / L, trisodium citrate 18 g / L, thiourea 0.5 mg / L, ammonium acetate 19 g / L; adjusting the pH of the plating solution to 4 with hydrochloric acid or sodium hydroxide solution, and using The mass percentage of hydrochloric acid solute for adjusting the pH of the plating solution is 30%, the mass percentage of sodium hydroxide solution solute is 30%, and the solvent is water; the water bath is kept at a constant temperature of 85° C.; the pretreated shell is then immersed in the chemical plating solution, and the plating is carried out at a constant temperature of 85° C. for 1 hour, the pH of the plating solution is tested every 10 minutes, and the pH of the plating solution is adjusted to 4 with hydrochloric acid or sodium hydroxide solution; after the chemical plating is completed, it is taken out, rinsed with clean water to remove the residual liquid on the surface of the shell, and blown dry to obtain the wear-resistant motor shell.
[0037] Example 4
[0038] A method for treating a wear-resistant motor housing, comprising the steps of:
[0039] (1) preparing an aqueous solution of cerium nitrate; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 25 g / L, and the solvent is water; adding ammonium carbonate to ammonia water to prepare a precipitant; the amount ratio of ammonium carbonate to ammonia water to prepare a precipitant is ammonium carbonate: ammonia water = 3 g: 100 mL, and the mass percentage of solute in the ammonia water is 25%; stirring the aqueous solution of cerium nitrate, adding hydrogen peroxide to the solution under stirring, continuing to stir the solution for 10 minutes after adding, and then adding zirconium oxynitrate to the solution under stirring, and stirring for another 10 minutes after adding. n, then add the precipitant to the solution under stirring, wherein the amount ratio of the aqueous solution of cerium nitrate, hydrogen peroxide, zirconium oxynitrate and precipitant is the aqueous solution of cerium nitrate: hydrogen peroxide: zirconium oxynitrate: precipitant = 100mL: 8mL: 8g: 15mL; wherein the mass percentage of the solute in the hydrogen peroxide is 5%; after adding the materials, heat in a water bath to 85°C, keep warm and stir for 3h, condense and reflux during the heat preservation process; precipitate, separate the solid and liquid, wash the solid phase with deionized water 3 times, and then calcine at 560°C for 1h to obtain a composite oxide powder;
[0040] (2) preparing an ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid; in the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid, the concentration of 3-(trihydroxysilyl)-1-propanesulfonic acid is 3 g / 100 mL, and the solvent is ethanol; soaking the composite oxide powder in ethanol, and the amount ratio of the composite oxide powder to ethanol is composite oxide powder: ethanol = 1 g: 50 mL; stirring and dispersing with ultrasonic wave for 20 minutes to obtain a suspension, and then The suspension is heated to 40° C. in a water bath and condensed and refluxed during the insulation process; the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid is added to the suspension under stirring, and the volume ratio of the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid to the suspension is 1:1; after the addition is completed, the stirring is continued at a constant temperature of 40° C. for 18 hours, and then the solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and dried at 80° C. for 10 hours to obtain chemically plated doped particles;
[0041] (3) Prepare an aqueous solution of glycine, wherein the concentration of glycine in the aqueous solution of glycine is 18 g / 100 mL, and the solvent is water; prepare an aqueous solution of O-methylisourea sulfate; wherein the concentration of O-methylisourea sulfate in the aqueous solution of O-methylisourea sulfate is 23 g / 100 mL, and the solvent is water; stir the aqueous solution of glycine, add the aqueous solution of O-methylisourea sulfate and the aqueous solution of lithium hydroxide to the solution under stirring, and after the addition is completed, ice bath to 3° C. for insulation, and stir at a constant temperature for 20 hours; add sodium nitrate and sodium nitrite, wherein the concentration of lithium hydroxide in the aqueous solution of lithium hydroxide is 6 g / 100 mL, and the solvent is water; the amount ratio of the aqueous solution of glycine, the aqueous solution of O-methylisourea sulfate, the aqueous solution of lithium hydroxide, sodium nitrate and sodium nitrite is the aqueous solution of glycine: the aqueous solution of O-methylisourea sulfate: the aqueous solution of lithium hydroxide: sodium nitrate: sodium nitrite = 100 mL: 100 mL: 50 mL: 10 g: 5 g; stir for 30 minutes to obtain a treated solution;
[0042] (4) The aluminum alloy (2A12 aluminum alloy) motor housing is sanded to remove the oxide scale, then immersed in acetone for 10 minutes for degreasing treatment, and after being taken out, the residual acetone is blown dry with an air gun, and immersed in a dilute nitric acid solution for 20 seconds for pickling activation, wherein the concentration of the solute in the dilute nitric acid solution is 1%; after activation, it is taken out and immersed in deionized water for ultrasonic immersion for 5 minutes, and then the residual liquid is taken out and blown dry, and immersed in the treatment solution at a constant temperature of 60° C. for 5 minutes to obtain a pre-treated housing;
[0043] (5) preparing a chemical plating solution, wherein the components of the chemical plating solution are nickel sulfate, sodium hypophosphite, the chemical plating doping particles, potassium iodide, trisodium citrate, thiourea and ammonium acetate, and the solvent is water; the concentrations of the components are: nickel sulfate 26 g / L, sodium hypophosphite 30 g / L, chemical plating doping particles 2 g / L, potassium iodide 5 mg / L, trisodium citrate 20 g / L, thiourea 0.5 mg / L, ammonium acetate 20 g / L; adjusting the pH of the plating solution to 4 with hydrochloric acid or sodium hydroxide solution, and using The mass percentage of hydrochloric acid solute for adjusting the pH of the plating solution is 30%, the mass percentage of sodium hydroxide solution solute is 30%, and the solvent is water; the water bath is kept at a constant temperature of 85° C.; the pretreated shell is then immersed in the chemical plating solution, and the plating is carried out at a constant temperature of 85° C. for 1 hour, the pH of the plating solution is tested every 10 minutes, and the pH of the plating solution is adjusted to 4 with hydrochloric acid or sodium hydroxide solution; after the chemical plating is completed, it is taken out, rinsed with clean water to remove the residual liquid on the surface of the shell, and blown dry to obtain the wear-resistant motor shell.
[0044] Comparative Example 1
[0045] A method for processing a motor housing as a comparison includes the following steps:
[0046] (1) preparing an aqueous solution of cerium nitrate; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 24 g / L, and the solvent is water; adding ammonium carbonate to ammonia water to prepare a precipitant; the amount ratio of ammonium carbonate to ammonia water to prepare a precipitant is ammonium carbonate: ammonia water = 3 g: 100 mL, and the mass percentage of solute in the ammonia water is 25%; stirring the aqueous solution of cerium nitrate, adding hydrogen peroxide to the solution under stirring, continuing to stir the solution for 10 minutes after adding, and then adding zirconium oxynitrate to the solution under stirring, stirring for another 10 minutes after adding, and then stirring under stirring The precipitant is added to the solution in a state, wherein the amount ratio of the aqueous solution of cerium nitrate, hydrogen peroxide, zirconium oxynitrate and precipitant is the aqueous solution of cerium nitrate: hydrogen peroxide: zirconium oxynitrate: precipitant = 100mL: 7mL: 8g: 14mL; wherein the mass percentage of the solute in the hydrogen peroxide is 5%; after the addition, the water bath is heated to 85°C, and the mixture is stirred for 3h at this temperature, and condensed and refluxed during the insulation process; the precipitate is precipitated, the solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and then calcined at 560°C for 1h to obtain a composite oxide powder as the chemical plating doped particles of this comparative example;
[0047] (2) Prepare an aqueous solution of glycine, wherein the concentration of glycine in the aqueous solution of glycine is 17 g / 100 mL, and the solvent is water; prepare an aqueous solution of O-methylisourea sulfate; wherein the concentration of O-methylisourea sulfate in the aqueous solution of O-methylisourea sulfate is 22 g / 100 mL, and the solvent is water; stir the aqueous solution of glycine, add the aqueous solution of O-methylisourea sulfate and the aqueous solution of lithium hydroxide to the solution under stirring, and after the addition is completed, ice bath to 3° C. for insulation, and stir at a constant temperature for 20 hours; add sodium nitrate and sodium nitrite, wherein the concentration of lithium hydroxide in the aqueous solution of lithium hydroxide is 6 g / 100 mL, and the solvent is water; the amount ratio of the aqueous solution of glycine, the aqueous solution of O-methylisourea sulfate, the aqueous solution of lithium hydroxide, sodium nitrate and sodium nitrite is the aqueous solution of glycine: the aqueous solution of O-methylisourea sulfate: the aqueous solution of lithium hydroxide: sodium nitrate: sodium nitrite = 100 mL: 100 mL: 50 mL: 9 g: 4 g; stir for 30 minutes to obtain a treated solution;
[0048] (3) The aluminum alloy (2A12 aluminum alloy) motor housing is sanded to remove the oxide scale, then immersed in acetone for 10 minutes for degreasing treatment, and after being taken out, the residual acetone is blown off with an air gun, and immersed in a dilute nitric acid solution for 20 seconds for pickling activation, wherein the concentration of the solute in the dilute nitric acid solution is 1%; after activation, it is taken out and immersed in deionized water for ultrasonic immersion for 5 minutes, and then the residual liquid is taken out and blown off, and immersed in the treatment solution at a constant temperature of 60° C. for 5 minutes to obtain a pre-treated housing;
[0049] (4) preparing a chemical plating solution, wherein the components of the chemical plating solution are nickel sulfate, sodium hypophosphite, the chemical plating doping particles, potassium iodide, trisodium citrate, thiourea and ammonium acetate, and the solvent is water; the concentrations of the components are: nickel sulfate 25 g / L, sodium hypophosphite 29 g / L, chemical plating doping particles 2 g / L, potassium iodide 4 mg / L, trisodium citrate 18 g / L, thiourea 0.5 mg / L, and ammonium acetate 19 g / L; adjusting the pH of the plating solution to 4 with hydrochloric acid or sodium hydroxide solution, and using The mass percentage of hydrochloric acid solute for adjusting the pH of the plating solution is 30%, the mass percentage of sodium hydroxide solution solute is 30%, and the solvent is water; the water bath is kept at a constant temperature of 85°C for heat preservation; then the pretreated shell is immersed in the chemical plating solution, and the plating is carried out at a constant temperature of 85°C for 1 hour, the pH of the plating solution is tested every 10 minutes, and the pH of the plating solution is adjusted to 4 with hydrochloric acid or sodium hydroxide solution; after the chemical plating is completed, it is taken out, rinsed with clean water to remove the residual liquid on the surface of the shell, and blown dry to obtain the motor shell of this comparative example.
[0050] Comparative Example 2
[0051] A method for processing a motor housing as a comparison includes the following steps:
[0052] (1) preparing an aqueous solution of cerium nitrate; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 24 g / L, and the solvent is water; adding ammonium carbonate to ammonia water to prepare a precipitant; the amount ratio of ammonium carbonate to ammonia water to prepare a precipitant is ammonium carbonate: ammonia water = 3 g: 100 mL, and the mass percentage of solute in the ammonia water is 25%; stirring the aqueous solution of cerium nitrate, adding hydrogen peroxide to the solution under stirring, continuing to stir the solution for 10 minutes after adding, and then adding zirconium oxynitrate to the solution under stirring, and stirring for another 10 minutes after adding. n, then add the precipitant to the solution under stirring, wherein the amount ratio of the aqueous solution of cerium nitrate, hydrogen peroxide, zirconium oxynitrate and precipitant is the aqueous solution of cerium nitrate: hydrogen peroxide: zirconium oxynitrate: precipitant = 100mL: 7mL: 8g: 14mL; wherein the mass percentage of the solute in the hydrogen peroxide is 5%; after adding the materials, heat to 85°C in a water bath, keep warm and stir for 3h, condense and reflux during the heat preservation process; precipitate, separate the solid and liquid, wash the solid phase with deionized water 3 times, and then calcine at 560°C for 1h to obtain a composite oxide powder;
[0053] (2) preparing an ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid; in the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid, the concentration of 3-(trihydroxysilyl)-1-propanesulfonic acid is 3 g / 100 mL, and the solvent is ethanol; soaking the composite oxide powder in ethanol, and the amount ratio of the composite oxide powder to ethanol is composite oxide powder: ethanol = 1 g: 50 mL; stirring and dispersing with ultrasonic wave for 20 minutes to obtain a suspension, and then The suspension is heated to 40° C. in a water bath and condensed and refluxed during the insulation process; the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid is added to the suspension under stirring, and the volume ratio of the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid to the suspension is 1:1; after the addition is completed, the stirring is continued at a constant temperature of 40° C. for 18 hours, and then the solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and dried at 80° C. for 10 hours to obtain chemically plated doped particles;
[0054] (3) The aluminum alloy (2A12 aluminum alloy) motor housing was sanded to remove the oxide scale, then immersed in acetone for 10 minutes for degreasing treatment, and after being taken out, the residual acetone was blown off with an air gun, and then immersed in a dilute nitric acid solution for 20 seconds for pickling activation, wherein the concentration of the solute in the dilute nitric acid solution was 1%; after activation, it was taken out and immersed in deionized water again for ultrasonic immersion for 5 minutes, and then the residual liquid was taken out and blown off to obtain the pre-treated housing of this comparative example;
[0055] (4) preparing a chemical plating solution, wherein the components of the chemical plating solution are nickel sulfate, sodium hypophosphite, the chemical plating doping particles, potassium iodide, trisodium citrate, thiourea and ammonium acetate, and the solvent is water; the concentrations of the components are: nickel sulfate 25 g / L, sodium hypophosphite 29 g / L, chemical plating doping particles 2 g / L, potassium iodide 4 mg / L, trisodium citrate 18 g / L, thiourea 0.5 mg / L, and ammonium acetate 19 g / L; adjusting the pH of the plating solution to 4 with hydrochloric acid or sodium hydroxide solution, and using The mass percentage of hydrochloric acid solute for adjusting the pH of the plating solution is 30%, the mass percentage of sodium hydroxide solution solute is 30%, and the solvent is water; the water bath is kept at a constant temperature of 85°C for heat preservation; then the pretreated shell is immersed in the chemical plating solution, and the plating is carried out at a constant temperature of 85°C for 1 hour, the pH of the plating solution is tested every 10 minutes, and the pH of the plating solution is adjusted to 4 with hydrochloric acid or sodium hydroxide solution; after the chemical plating is completed, it is taken out, rinsed with clean water to remove the residual liquid on the surface of the shell, and blown dry to obtain the motor shell of this comparative example.
[0056] Example 5
[0057] The surface hardness of the plated surface was tested by a micro Vickers hardness tester with a loading load of 2 N and a loading time of 5 s. Five points were randomly selected for testing on each sample and the average value was taken. The motor housing (2A12 aluminum alloy) without plating was used as the control group, and the results are shown in Table 1.
[0058] It can be seen from Table 1 that after the high thermal conductivity aluminum alloy motor housing is treated by the method of the present invention, the problem of low surface hardness and poor wear resistance of the aluminum alloy is solved, and the surface hardness is significantly improved. By comparing Example 3 of the present invention and the comparative examples, it can be seen that by adding chemical plating doping particles during the plating process, or pre-treating the surface of the aluminum alloy substrate before plating, the surface hardness of the coating can be significantly improved. This is mainly because: the present invention first obtains chemical plating doping particles with a high specific surface area by doping cerium in zirconium oxide, so that the bonding surface between the doped particles and the coating in the subsequent coating is larger and the bonding is more firm, and doping with cerium is conducive to optimizing the surface state of the particles, providing conditions for the subsequent modification process of the particles. The particles are then modified by 3-(trihydroxysilyl)-1-propanesulfonic acid to form sulfonic acid functional groups on the particle surface, which is beneficial to the binding and deposition of the particles on the surface of the motor housing during subsequent plating. In addition, the motor housing is pretreated by glycine, O-methylisourea sulfate, etc. to form an amino-containing pretreatment layer on the housing surface, which is more conducive to the formation of the coating and the adsorption of chemically plated doped particles during the plating process, forming a stable and dense tin-plated coating containing doped particles, thereby improving the wear resistance of the housing surface.
[0059] Table 1
[0060]
[0061] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A method for treating a wear-resistant motor housing, characterized in that the steps include: (1) preparing an aqueous solution of cerium nitrate; adding ammonium carbonate to ammonia water to prepare a precipitant; stirring the aqueous solution of cerium nitrate, adding hydrogen peroxide to the solution under stirring, continuing to stir the solution to mix evenly after adding, then adding zirconium oxynitrate to the solution under stirring, stirring and mixing evenly after adding, then adding the precipitant to the solution under stirring, heating to 60-90° C. in a water bath after adding, stirring and precipitating, separating the solid from the liquid, washing the solid phase with deionized water, and then calcining at 560-600° C. for 1-2 hours to obtain a composite oxide powder; (2) preparing an ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid; immersing the composite oxide powder in ethanol, dispersing it by ultrasonic stirring to obtain a suspension, then heating the suspension in a water bath to 40±5° C. and keeping it warm, condensing and refluxing during the insulation process; then adding the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid to the suspension under stirring, and continuing to stir at a constant temperature of 40±5° C. for more than 18 hours after the addition is completed, then separating the solid from the liquid, washing the solid phase with deionized water, and drying to obtain chemically plated doped particles; (3) preparing an aqueous solution of glycine and an aqueous solution of O-methylisourea sulfate; stirring the aqueous solution of glycine, adding the aqueous solution of O-methylisourea sulfate and the aqueous solution of lithium hydroxide to the solution under stirring, and after the addition is completed, ice-bathing to 0-5° C. and maintaining the temperature, stirring at the constant temperature for more than 20 hours; then adding sodium nitrate and sodium nitrite, stirring for more than 30 minutes to obtain a treated solution; (4) The aluminum alloy motor housing is polished with sandpaper to remove the oxide scale, and then degreased with a degreasing agent. After taking it out, the residual degreasing agent is blown away with an air gun, and then immersed in a dilute nitric acid solution for pickling activation. After activation, the clean acid solution is taken out, and the residual solution is blown away, and then immersed in the treatment solution at a constant temperature of 50 to 70° C. for 4 to 5 minutes to obtain a pre-treated housing; (5) preparing a chemical plating solution, wherein the components of the chemical plating solution are nickel sulfate, sodium hypophosphite, the chemical plating doping particles, potassium iodide, trisodium citrate, thiourea and ammonium acetate, and the solvent is water; adjusting the pH of the chemical plating solution to 3.5-4.5 with hydrochloric acid or sodium hydroxide solution, and maintaining the temperature at 85±5° C. in a water bath; then immersing the pretreated shell in the chemical plating solution, plating at a constant temperature of 85±5° C. for 1-2 hours, testing the pH of the plating solution every 5-15 minutes, and adjusting the pH of the plating solution to 3.5-4.5 with hydrochloric acid or sodium hydroxide solution; After the chemical plating is completed, the shell is taken out, rinsed with clean water to remove the residual liquid on the surface of the shell, and blown dry to obtain the wear-resistant motor shell.
2. A method for treating a wear-resistant motor housing according to claim 1, characterized in that: In the step (1), the concentration of cerium nitrate in the aqueous solution of cerium nitrate is 20-25 g / L, and the solvent is water; the amount ratio of ammonium carbonate added to ammonia water to prepare a precipitant is ammonium carbonate: ammonia water = 2-3 g: 100 mL, and the mass percentage of solute in the ammonia water is 25%; the amount ratio of the aqueous solution of cerium nitrate, hydrogen peroxide, zirconium oxynitrate, and precipitant is cerium nitrate aqueous solution: hydrogen peroxide: zirconium oxynitrate: precipitant = 100 mL: 6-8 mL: 7-8 g: 10-15 mL; wherein the mass percentage of solute in the hydrogen peroxide is 5%.
3. The method for treating a wear-resistant motor housing according to claim 1, characterized in that: In the step (2), the concentration of 3-(trihydroxysilyl)-1-propanesulfonic acid in the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid is 2 to 3 g / 100 mL, and the solvent is ethanol; the amount ratio of the composite oxide powder immersed in ethanol is composite oxide powder: ethanol = 1 to 2 g: 50 mL; the volume ratio of adding the ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid to the suspension is suspension: ethanol solution of 3-(trihydroxysilyl)-1-propanesulfonic acid = 1:
1.
4. The method for treating a wear-resistant motor housing according to claim 1, characterized in that: In the step (3), the concentration of glycine in the aqueous solution is 16-18 g / 100 mL, and the solvent is water; the concentration of O-methylisourea sulfate in the aqueous solution is 20-23 g / 100 mL, and the solvent is water; the concentration of lithium hydroxide in the aqueous solution is 5-6 g / 100 mL, and the solvent is water; the amount ratio of the aqueous solution of glycine, the aqueous solution of O-methylisourea sulfate, the aqueous solution of lithium hydroxide, sodium nitrate and sodium nitrite is glycine aqueous solution: O-methylisourea sulfate aqueous solution: lithium hydroxide aqueous solution: sodium nitrate: sodium nitrite = 100 mL: 100 mL: 40-50 mL: 8-10 g: 3-5 g.
5. The method for treating a wear-resistant motor housing according to claim 1, characterized in that: In the step (4), the concentration of the solute in the dilute nitric acid solution is 1%.
6. A method for treating a wear-resistant motor housing according to claim 1, characterized in that: In the step (5), the concentration of each component in the chemical plating solution is: nickel sulfate 24-26 g / L, sodium hypophosphite 28-30 g / L, chemical plating doping particles 1-2 g / L, potassium iodide 3-5 mg / L, trisodium citrate 15-20 g / L, thiourea 0.5 mg / L, ammonium acetate 18-20 g / L; the mass percentage of hydrochloric acid solute used to adjust the pH of the plating solution is 30%, the mass percentage of sodium hydroxide solution solute is 30%, and the solvent is water.
Citation Information
Patent Citations
Zirconium oxide-based corrosion-resistant and wear-resistant coating on magnesium alloy surface and preparation method thereof
CN114351125A
Electroless zirconium plating solutions
KR1020120105232A